2014
DOI: 10.1016/j.jpsychires.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma eicosapentaenoic acid levels are associated with elevated trait aggression and impulsivity in major depressive disorder with a history of comorbid substance use disorder

Abstract: Major depressive disorder (MDD) is associated with low levels of omega-3 polyunsaturated fatty acids (PUFAs), holding promise for new perspectives on disease etiology and treatment targets. As aggressive and impulsive behaviors are associated with low omega-3 PUFA levels in some clinical contexts, we investigated plasma PUFA relationships with trait aggression and impulsivity in patients with MDD. Medication-free MDD patients (n=48) and healthy volunteers (HV, n=35) were assessed with the Brown-Goodwin Aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…For example, a study investigating the potential reduction in child and adolescent antisocial and aggressive behavior with omega‐3 supplementation, including the essential fatty acid alpha‐linolenic acid (αLA), reported significant declines in self‐reported reactive and proactive aggression after omega‐3 supplementation [Raine et al, ]. Various other studies have reported similar beneficial effects of omega‐3 supplementation on aggression in other populations, including young adult men [Long and Benton, ] and females with BPD [Zanarini and Frankenburg, ], in contrast, other studies reported increased aggression after omega‐3 supplementation, including populations of school‐aged children [Itomura et al, ] and patients with comorbid major depressive disorder and substance use disorder [Beier et al, ]. While these kinds of supplement studies identify fatty acid metabolism as a possible mechanism underlying aggressive behavior, metabolomics studies might be able to determine which of the fatty acids included in the supplements have a positive influence on the reduction of aggressive behavior.…”
Section: Metabolomics Approaches To Biochemical Biomarker Discoverymentioning
confidence: 99%
“…For example, a study investigating the potential reduction in child and adolescent antisocial and aggressive behavior with omega‐3 supplementation, including the essential fatty acid alpha‐linolenic acid (αLA), reported significant declines in self‐reported reactive and proactive aggression after omega‐3 supplementation [Raine et al, ]. Various other studies have reported similar beneficial effects of omega‐3 supplementation on aggression in other populations, including young adult men [Long and Benton, ] and females with BPD [Zanarini and Frankenburg, ], in contrast, other studies reported increased aggression after omega‐3 supplementation, including populations of school‐aged children [Itomura et al, ] and patients with comorbid major depressive disorder and substance use disorder [Beier et al, ]. While these kinds of supplement studies identify fatty acid metabolism as a possible mechanism underlying aggressive behavior, metabolomics studies might be able to determine which of the fatty acids included in the supplements have a positive influence on the reduction of aggressive behavior.…”
Section: Metabolomics Approaches To Biochemical Biomarker Discoverymentioning
confidence: 99%
“…Highly unsaturated long-chain PUFAs arachidonic acid (AA, 20:4n-6) and docosahexaenoic acid (DHA, 22:6n-3), are the major constituents of brain PUFAs, and have been implicated in psychiatric illness, including major depression (29), bipolar disorder (30, 31) and suicide risk (3234). Eicosapentaenoic acid (EPA, 20:5n-3), although present in considerably lower quantities in brain as a result of its rapid β-oxidation and metabolism (3537), also is reported to have specific effects related to neuropsychiatric conditions (3843). …”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined a possible relationship between PUFAs and BIS-11 scores, but to date, no publication has specifically evaluated this in gambling disorder [18][19][20]. The scarce studies in this field, which evaluate a possible effect of fatty acid supplementation on BIS-11 scores, show no enlightening results [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the possible association between basal PUFA composition and scores on the BIS-11, we only found published studies evaluating PUFA in plasma, and none of which evaluates the erythrocyte membrane composition [18][19][20]. This is striking, considering this method (the composition of PUFA in erythrocyte membrane) is better than the plasma concentration or composition, to provide in clinical practice, a reliable estimate of the basal PUFA values [12], and precisely, this is one of the strengths of the present study.…”
Section: Introductionmentioning
confidence: 99%